Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Queer - Getsy, David (Whitechapel : documents of contemporary art, 2016)
"Rather than a book of queer theory for artists, this is a book of artists' queer tactics and infectious concepts. In the first such anthology to be centred on artists' writings, numerous conversations about queer practice are brought together from diverse individual, social and cultural contexts. Together these texts describe and examine the ways in which artists have used the concept of queer as a site of political and institutional critique, as a framework to develop new families and histories, as a spur to action, and as a basis from which to declare inassimilable difference"--Back cover.
Keywords: LGBTQIA2+; approches et analyses; arts; arts visuels et médiatiques; cours; critique institutionelle; critique politique; discipline; har4600; identités LGBTQIA2+; intersectionnalité; militance; pratique artistique; premier cycle; queer; thématiques; écrits d'artiste